"Be Less of a Slave to the News": A Texto-Material Perspective on News Avoidance among Young Adults. (2nd January 2021) - Aharoni, Tali; Kligler-Vilenchik, Neta; Tenenboim-Weinblatt, Keren
ABSTRACT: The distinct media repertoire of young adults in the digital age, especially their increasing ability to bypass the news media, inspires a wealth of research. While previous studies have focused on social- and content-related motivations to avoid the news, we have yet to fully understand the interplay of such motivations with material, technology-related considerations. Drawing on 36 in-depth interviews with Israeli young adults, this paper explores the varied motivations of young audiences to avoid the news through a texto-material conceptualization of news avoidance as directed at both contents and objects. An inductive-qualitative analysis of young adults' media consumption narratives identified three main dimensions: content, medium, and user-oriented news avoidance. The study demonstrates the material aspects of both deliberate and unintentional news avoidance, and how they relate to content-oriented considerations. Furthermore, the Israeli socio-political context reveals that in times of crisis, these motivations are shared by both heavy and light news consumers. Taken together, the different avoidance motivations and practices identified in this study provide an analytical framework to further understand news avoidance and design differentiated strategies to address young adults' disengagement from news.